Gastric-type Mucinous Carcinoma with an Abnormal Increase of CA199: A Case Report and Literature Review - Qian, Xue-qian; Wang, Fen-fen; Liang, Yun; Chen, Li-Li; Wan, Xiao-yun (Frontiers in Surgery, 2022)
Abstract Objective Gastric-type mucinous carcinoma (GAS), as a rare subtype of mucinous adenocarcinoma, accounts for approximately 1%-3% of cervical adenocarcinoma. It was considered as a new type of cervical mucinous adenocarcinoma in the World Health Organization（WHO）in 2014. GAS represents more aggressive disease than does usual type endocervical adenocarcinoma (UEA) . Case report A case of cervical adenocarcinoma with abnormal increase of CA199 in a 50-year-old Chinese woman was reported. Our patient presented with abnormal vaginal discharge and combined with elevated Ca199 at the value of 2729 U/ml. Imaging examinations showed no abnormalities. Diagnostic conical resection suggested cervical adenocarcinoma in situ. Postoperative pathology confirmed mucinous cervical adenocarcinoma (considering gastric type), infiltrating cervical interstitial > 2/3, involving deep myometrium, accompanied by vascular carcinoma infiltration and lymph node metastasis. The patients received an extensive hysterectomy and postoperative adjuvant chemoradiotherapy. The chemotherapy regimen was paclitaxel combined with platinum. After 20 months of follow-up, the patient showed no signs of recurrence. Conclusion Preoperative diagnosis of cervical adenocarcinoma is insidious and easy to be misdiagnosed. For patients with high preoperative Ca199, the possibility of GAS should be kept alert. Keywords: Cervical adenocarcinoma in situ，Cervical adenocarcinoma，Gastric-type mucinous carcinoma (GAS) ，Ca199